Aerospace marketing management : a handbook for the entire value chain - Malaval, Philippe; Bénaroya, Christophe; Aflalo, Jonathan (Management for Professionals,, 2014)
This book presents an overall picture of both B2B and B2C marketing strategies, concepts and tools, in the aeronautics sector. This is a significant update to an earlier book successfully published in the nineties which was released in Europe, China, and the USA. It addresses the most recent trends such as Social Marketing and the internet, Customer Orientation, Project Marketing and Con current Engineering, Coopetition, and Extended Enterprise. Aerospace Marketing Management is the first marketing handbook richly illustrated with executive and expert inputs as well as examples from parts suppliers, aircraft builders, airlines, helicopter manufacturers, aeronautics service providers, airports, defence and military companies, and industrial integrators (tier-1, tier-2). This book is designed as a ready reference for professionals and graduates from both Engineering and Business Schools.